An Economic Theory of Disinformation - HARASHIMA, Taiji (Theoretical and Practical Research in Economic Fields; Vol 14 No 1 (2023): TPREF, Volume XIV, Issue 1(27), Summer 2023, 2023)
The impacts of misinformation and disinformation have rarely been studied in economics. In this paper, I examine these impacts using a model constructed on the basis of the concept of ranked information. The value of information is changeable and differs across people; therefore, disinformation can be used as a tool to manipulate people’s behaviors. I first define misinformation and disinformation and then show the mechanism through which disinformation decreases efficiency by manipulating ranked information. Decreases in efficiency are observed as decreases in total factor productivity, lowered success rates of investment, and increased costs of bad speculations. In addition, disinformation generates economic rents and, as a result, increases inequality, possibly by a great deal. Furthermore, disinformation can cause large-scale economic fluctuations.